First, break all the rules what the World's greatest managers do differently - Buckingham, Marcus (Michigan Brilliance Audio, 2016)
Learn how the best managers select an employee for talent rather than for skills or experience, how they set expectations for him or her, how they motivate people, and how great managers develop people.
Keywords: Executive ability